Análise temporal da dieta de toninha (Cetartiodactyla: Pontoporia blainvillei) na FMA IIb, sudeste do Brasil - Grellet, Gabriel Mendonça [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
In the Western South Atlantic, the franciscana (Pontoporia blainvillei) is a species of small coastal dolphin, threatened by indcidental catch in fishing gillnets. Information about the species' feeding habits is still scarce in the northern portion of its distribution (FMAs I and II). This study aimed to describe and evaluate the importance its feeding habits by analyzing the stomach contents of 206 carcasses from strandings and incidental captures between the years 2015 and 2021, on the south-central coast of São Paulo. We identified 6932 otoliths and 1126 cephalopod beaks, totaling 20 prey taxa identified: 17 teleosts and 3 cephalopods. The species that presented the highest index of relative importance (∑IRI > 90%) were respectively Stellifer rastrifer; Pellona harroweri; Doryteuthis plei; Lolliguncula brevis; and Paralonchurus brasiliensis. Thus franciscanas presented piscivorous and teutophagous habits. The greater contribution of S. rastrifer to the diet differs from previous studies conducted in the same region. We did not record significant differences between the importance of these species for sexes, ages and seasons. The temporal analysis of the diet showed a significant difference between the years studied.

No Atlântico Sul Ocidental, a toninha (Pontoporia blainvillei), espécie de pequeno golfinho costeiro, está ameaçada pelo emalhe acidental em redes de pesca. Informações sobre os hábitos alimentares da espécie ainda são escassas na porção norte de sua distribuição (FMAs I e II). Este estudo se propôs a descrever e avaliar a dieta através da análise do conteúdo estomacal de 206 carcaças oriundas de encalhes e capturas acidentais entre os anos de 2015 a 2021, no litoral centro-sul de São Paulo. A espécie apresentou hábitos alimentares piscívoros e teutófagos. Identificamos 6932 otólitos e 1126 bicos de cefalópodes presentes no conteúdo estomacal. Totalizando 20 táxons de presas identificadas: 17 de peixes teleósteos e 3 de cefalópodes. As espécies que apresentaram maior índice de importância relativa (∑IRI > 90%): foram respectivamente Stellifer rastrifer; Pellona harroweri; Doryteuthis plei; Lolliguncula brevis; e Paralonchurus brasiliensis. A maior contribuição de S. rastrifer na dieta difere de estudos prévios conduzidos na mesma região. Não registramos diferenças significativas entre as importâncias destas espécies para os sexos, idades e estações. A análise temporal da dieta apresentou diferença significativa entre os anos estudados.
Temporal Analyses over franciscanas (Cetartiodactyla: Pontoporia blainvillei) feeding habits, on Franciscana Management Area IIb, southeast Brazil.
Keywords: Trophic ecology; Feeding habits; Small dolphin; Coastal cetacean; Stomach content; Ecologia trófica; Hábitos alimentares; Cetáceos; Toninhas